Wound- and mechanostimulated electrical signals control hormone responses - Farmer, Edward E.; Gao, Yong-Qiang; Lenzoni, Gioia; Wolfender, Jean-Luc; Wu, Qian (The New phytologist, 2020)
Plants in nature are constantly exposed to organisms that touch them and wound them.A highly conserved response to these stimuli is a rapid collapse of membrane potential (i.e. a decrease of electrical field strength across membranes). This can be coupled to the production and/or action of jasmonate or ethylene. Here, the various types of electrical signals in plants are discussed in the context of hormone responses. Genetic approaches are revealing genes involved in wound-induced electrical signalling. These include clade 3 GLUTAMATE RECEPTOR-LIKE (GLR) genes, Arabidopsis H⁺-ATPases (AHAs), RESPIRATORY BURST OXIDASE HOMOLOGUEs (RBOHs), and genes that determine cell wall properties. We briefly review touch- and wound-induced increases in cytosolic Ca2+ concentrations and their temporal relationship to electrical activities. We then look at the questions that need addressing to link mechanostimulation and wound-induced electrical activity to hormone responses. Utilizing recently published results, we also present a hypothesis for wound-response leaf-to-leaf electrical signalling. This model is based on rapid electro-osmotic coupling between the phloem and xylem. The model suggests that the depolarization of membranes within the vascular matrix triggered by physical stimuli and/or chemical elicitors is linked to changes in phloem turgor and that this plays vital roles in leaf-to-leaf electrical signal propagation.